2016
DOI: 10.1007/s10071-015-0948-z
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Initiation of joint travel in mother–infant dyads of two chimpanzee communities in the wild

Abstract: It is well established that great apes communicate via intentionally produced, elaborate and flexible gestural means. Yet relatively little is known about the most fundamental steps into this communicative endeavour—communicative exchanges of mother–infant dyads and gestural acquisition; perhaps because the majority of studies concerned captive groups and single communities in the wild only. Here, we report the first systematic, quantitative comparison of communicative interactions of mother–infant dyads in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(146 citation statements)
references
References 68 publications
11
135
0
Order By: Relevance
“…It is, however, not clear whether the hand-clasp qualifies as gesture, since its communicative function is still debated [82] and it might simply act as a stabilizing tool. Our findings provide further support for the social negotiation hypothesis proposed by Fröhlich et al [36] which postulates that gestures originate from the exchange of social behaviours resulting in a mutual recognition that (i) certain behaviours can be used communicatively, (ii) carry distinct meaning linked to particular social contexts, and (iii) are produced to achieve distinct goals. However, further fine-grained analyses of great ape gestural production are necessary to reveal the form of gestures in relation to age, context and social partner.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…It is, however, not clear whether the hand-clasp qualifies as gesture, since its communicative function is still debated [82] and it might simply act as a stabilizing tool. Our findings provide further support for the social negotiation hypothesis proposed by Fröhlich et al [36] which postulates that gestures originate from the exchange of social behaviours resulting in a mutual recognition that (i) certain behaviours can be used communicatively, (ii) carry distinct meaning linked to particular social contexts, and (iii) are produced to achieve distinct goals. However, further fine-grained analyses of great ape gestural production are necessary to reveal the form of gestures in relation to age, context and social partner.…”
Section: Discussionsupporting
confidence: 87%
“…If an asymptote was reached (i.e. no further gesture types were observed), we concluded that we had observed the individual's full repertoire for the communicative function of play solicitation [36]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations